2017
DOI: 10.1111/jfb.13448
|View full text |Cite
|
Sign up to set email alerts
|

Squalus bassi sp. nov., a new long‐snouted spurdog (Chondrichthyes: Squaliformes: Squalidae) from the Agulhas Bank

Abstract: The long-snouted African spurdog Squalus bassi sp. nov. is described based on material collected from the outer shelf and upper continental slope off South Africa and Mozambique. Squalus bassi shares with S. mitsukurii, S. montalbani, S. chloroculus, S. grahami, S. griffini, S. edmundsi, S. quasimodo and S. lobularis a large snout with prenarial length greater than distance between nostrils and upper labial furrows, dermal denticles tricuspidate and rhomboid and elevated number of vertebrae. Squalus bassi can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Squalus mitsukurii is supported here as a regional endemic species to the North-western Pacific Ocean, which is in disagreement with Schroeder (1948, 1957), Bass et al (1976), Compagno (1984) and Compagno et al (2005a) and which was previously known as cosmopolitan. This result is congruent with recent taxonomic investigations on this species of Viana et al (2017b), Veríssimo et al (2017), Pfleger et al (2018) and Daly-Engel et al (2018) who refuted the occurrence of S. mitsukurii in the Western Indian, Western and Eastern Atlantic Oceans. The present analysis also rejects the occurrence of S. mitsukurii in Hawaiian waters given the validity of S. hawaiiensis, as supported in Daly-Engel et al (2018) and in the diagnosis and remarks above.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Squalus mitsukurii is supported here as a regional endemic species to the North-western Pacific Ocean, which is in disagreement with Schroeder (1948, 1957), Bass et al (1976), Compagno (1984) and Compagno et al (2005a) and which was previously known as cosmopolitan. This result is congruent with recent taxonomic investigations on this species of Viana et al (2017b), Veríssimo et al (2017), Pfleger et al (2018) and Daly-Engel et al (2018) who refuted the occurrence of S. mitsukurii in the Western Indian, Western and Eastern Atlantic Oceans. The present analysis also rejects the occurrence of S. mitsukurii in Hawaiian waters given the validity of S. hawaiiensis, as supported in Daly-Engel et al (2018) and in the diagnosis and remarks above.…”
Section: Discussionsupporting
confidence: 91%
“…Single or combined taxonomic evidence (e.g. morphological and molecular data) have supported current and constant changes in the taxonomy of S. mitsukurii as seen in Viana et al (2017b), Pfleger et al (2018), Daly-Engel et al (2018) and Dolganov (2019). Thus, reporting occurrences of this species elsewhere, including Nazca and Sala y Gomez seamounts, Chile, India, Mexico (east coast), Costa Rica, Madagascar, Colombia and Uruguay in Parin (1987), Dyer and Westneat (2010), Akhilesh et al (2014), Del Moral-Flores et al (2015, Ehemann et al (2018), Espinoza et al (2018), Fricke et al (2018), Mejía-Falla andNavia (2019) and Nión and Meneses (2016) require taxonomic clarification.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The haplotype network revealed that S. japonicus, S. edmundsi, and S. grahami did not share haplotypes, unlike S. clarkae and S. mitsukurii, which did. Squalus mitsukurii was originally described in Japan by Jordan and Snyder (1903), and despite identification issues due to morphological character overlapping, this species presents a circumglobal distribution [69], and its occurrence has likely been overestimated [4,70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Species belonging to the family Squalidae have been under taxonomic revision in recent years, reporting species complexes and describing new species in the area (Bellodi et al, ; Pfleger et al, ; Viana et al, , ; Viana & De Carvalho, ). S. quasimodo has recently been added to the VEEZ, denoting that the species has probably been confused and reported as S. acanthias (L. 1758).…”
Section: Discussionmentioning
confidence: 99%